(untitled) (Journal of Academic Research, 2025)
Short abstract. This paper aims to explore the concept of kinship, clarify its types, and present jurisprudential opinions on the role of kinship in waiving had punishments.it also seeks to examine the stance of Libyan legislation on the waiver of had punishments due to kinship. The study adopts an inductive, descriptive,and comparative analytical approach, aligning with jurisprudential opinions in Islamic law. The research question revolves around the extent to which kinship affects the punishment for theft under Libyan law. The study concludes that kinship plays a role in waiving the had punishment for theft to preserve family unity and prevent discord. It reveals that Libyan legislation, specifically in the laws concerning the enforcement of had punishments for theft and hirabah, has narrowed the scope of kinship to include only ascendants,descendants,and mahram reiatives. Unlike the Libyan penal code, which extends kinship to include siblings, and their children.the research also that Libyan 10 of 2006 ,explicitly ack now theft.however, the study 10 of 2001 did not address , to jurisprudential and judicial disagreement.